Microcredit and poverty reduction: the role of entrepreneurial self-efficacy: empirical evidence from Kano, Northwest Nigeria - Kura, Shehu; Yahaya, Sani; Aliyu, Akilu; Ahmed, Ibrahim; Abdullahi, Muhammed; Bashiru, Suleiman (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
Purpose: The African continent houses a greater percentage of the global poor. Despite the well-articulated Sustainable Development Goals (SDGs) the continent was projected to constitute the largest percentage of the world's poor by 2030. The level of Africa’s poverty may not be divorced from its financial exclusion, as more than 80 percent of African households are excluded from formal financial services. The unbanked poor are exploited by informal financial service providers who effectively turn their customers into victims due to unfavorable loan terms. The establishment of several financial intervention programs was directed towards protecting the poor from informal money lenders' inhumane exploitation that stifles the desire of the poor to engage in income-generating activities. Findings on the effectiveness of these intervention programs are inconsistent. The aim of this paper is to empirically investigate the influence of microcredit on poverty reduction in Kano State, Northwest, Nigeria, using Entrepreneurial Self-efficacy as a moderator. Methodology: To achieve this, a model was developed and empirically tested using responses elicited with a structured questionnaire administered to 400 respondents drawn from eight microfinance banks (MFBs) using stratified sampling techniques. Results and conclusion: The study found a positive association between microcredit and poverty reduction. Also, entrepreneurial self-efficacy moderates the relationship between microcredit and poverty reduction in the study area. The paper concluded that microcredit, though not a silver bullet, is a veritable tool for poverty reduction. Implication of findings: The paper recommended additional commitment from government and NGOs in areas of microcredit provision as a tool for poverty reduction.